2023
DOI: 10.1002/jnr.25176
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐dependent structural neuroplasticity after a spatial navigation task: A diffusion imaging study

Abstract: Evidence for sleep-dependent changes in micro-structural neuroplasticity remains scarce, despite the fact that it is a mandatory correlate of the reorganization of learning-related functional networks. We investigated the effects of post-training sleep on structural neuroplasticity markers measuring standard diffusion tensor imaging (DTI) mean diffusivity (MD) and the revised biophysical neurite orientation dispersion and density imaging (NODDI) free water fraction (FWF) and neurite density (NDI) parameters th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 66 publications
3
6
4
Order By: Relevance
“…Finally, ODI changes in a few clusters, again in analogous regions, also suggest tissue reorganization in the brain tissue microstructure, even if at a smaller scale. Interestingly, although MD decreases have been repeatedly reported in the neocortex following learning, 28 , 30 , 56 a previous study using NODDI to investigate spatial learning-related structural plasticity observed FWF decreases but no NDI increase contrary to our results. 56 Besides task differences, this might be due to the fact that we used the revised version 57 , 58 instead of the original NODDI model 32 used in this preceding experiment, probably giving us the opportunity to gain in preciseness when it comes to disentangling the different components influencing MD alterations.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, ODI changes in a few clusters, again in analogous regions, also suggest tissue reorganization in the brain tissue microstructure, even if at a smaller scale. Interestingly, although MD decreases have been repeatedly reported in the neocortex following learning, 28 , 30 , 56 a previous study using NODDI to investigate spatial learning-related structural plasticity observed FWF decreases but no NDI increase contrary to our results. 56 Besides task differences, this might be due to the fact that we used the revised version 57 , 58 instead of the original NODDI model 32 used in this preceding experiment, probably giving us the opportunity to gain in preciseness when it comes to disentangling the different components influencing MD alterations.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, ODI changes in a few clusters, again in analogous regions, also suggest tissue reorganization in the brain tissue microstructure, even if at a smaller scale. Interestingly, although MD decreases have been repeatedly reported in the neocortex following learning, 28,30,56 a previous study using NODDI to investigate spatial learningrelated structural plasticity observed FWF decreases but no NDI increase contrary to our results. 56 Besides task differences, this might be due to the fact that we used the revised version 57,58 instead of the original NODDI model 32 used in this preceding experiment, probably giving us the opportunity to gain in preciseness when it comes to disentangling the different components influencing MD alterations.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, although MD decreases have been repeatedly reported in the neocortex following learning, 28,30,56 a previous study using NODDI to investigate spatial learningrelated structural plasticity observed FWF decreases but no NDI increase contrary to our results. 56 Besides task differences, this might be due to the fact that we used the revised version 57,58 instead of the original NODDI model 32 used in this preceding experiment, probably giving us the opportunity to gain in preciseness when it comes to disentangling the different components influencing MD alterations. Then, in subcortical regions of interest, decreased MD was found in the left putamen, right thalamus and caudate, bilateral hippocampus, and cerebellar cortex, together with increased FA in the right caudate and cerebellar cortex.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have explored the structural and functional alterations that accompany learning using structural and functional magnetic resonance imaging (MRI), respectively. Over the last decade, diffusion-weighted MRI (dMRI) has also been employed to study short-term microstructural neuroplasticity (Brodt et al, 2018; Hofstetter et al, 2017; Jacobacci et al, 2020; Keller and Just, 2016; Sagi et al, 2012; Tavor et al, 2020, 2013; Villemonteix et al, 2023). dMRI measures the translational displacement of water molecules (Bihan and Warach, 1995) and is mainly used for white matter assessment and reconstruction (Catani et al, 2002; Moseley et al, 1990; Warach et al, 1992).…”
Section: Introductionmentioning
confidence: 99%